Rho GTPases as Key Molecular Players within Intestinal Mucosa and GI Diseases - Rashmita Pradhan; Phuong A. Ngo; Luz d. C. Martínez-Sánchez; Markus F. Neurath; Rocío López-Posadas (Cells, 2021)
Rho proteins operate as key regulators of the cytoskeleton, cell morphology and trafficking. Acting as molecular switches, the function of Rho GTPases is determined by guanosine triphosphate (GTP)/guanosine diphosphate (GDP) exchange and their lipidation via prenylation, allowing their binding to cellular membranes and the interaction with downstream effector proteins in close proximity to the membrane. A plethora of in vitro studies demonstrate the indispensable function of Rho proteins for cytoskeleton dynamics within different cell types. However, only in the last decades we have got access to genetically modified mouse models to decipher the intricate regulation between members of the Rho family within specific cell types in the complex in vivo situation. Translationally, alterations of the expression and/or function of Rho GTPases have been associated with several pathological conditions, such as inflammation and cancer. In the context of the GI tract, the continuous crosstalk between the host and the intestinal microbiota requires a tight regulation of the complex interaction between cellular components within the intestinal tissue. Recent studies demonstrate that Rho GTPases play important roles for the maintenance of tissue homeostasis in the gut. We will summarize the current knowledge on Rho protein function within individual cell types in the intestinal mucosa in vivo, with special focus on intestinal epithelial cells and T cells.